BMPD-Assisted Enhancement of Corrosion Resistance of Carbon Steel: Experimental and First-Principle DFTB Insights - Omar Id El Mouden; Aisha H. Al-Moubaraki; Maryam Chafiq; Mohamed Bakhouch; Ahmed Batah; Lahcen Bammou; M’hammed Belkhaouda; Abdelkarim Chaouiki; Young Gun Ko (Metals, 2024)
Green corrosion inhibitors are gaining recognition for their sustainable, cost-effective, and environmentally friendly nature, along with their impressive water solubility and high corrosion inhibition efficiency. They offer a promising solution to combat corrosion issues that plague various industries. However, to harness the full potential of these eco-friendly corrosion inhibitors, a profound understanding of their development and underlying mechanisms is essential. This knowledge is the key to paving the way for the next generation of corrosion protection materials. Herein, a comprehensive study was conducted to understand the adsorption, corrosion inhibition efficiency, and stability of 3-benzoyl-4-hydroxy-2,6-bis(4-methoxyphenyl)-4-phenylcyclohexane-1,1-dicarbonitrile (BMPD). This study investigated the performance of BMPD applied to carbon steel (CS) in 1 M hydrochloric acid (HCl) solution. The corrosion inhibition effect was examined using weight loss, potentiodynamic polarization (PDP), electrochemical impedance spectroscopy (EIS), and theoretical studies. The surface morphology was also characterized and Tafel polarization analysis shows that BMPD is a mixed inhibitor. The results obtained by electrochemical impedance spectroscopy indicate that the inhibitory effect increases with increasing inhibitor concentration. The adsorption of BMPD on a CS surface obeyed the Langmuir adsorption isotherm. Thermodynamic parameters were calculated and discussed. Furthermore, this study involved a comprehensive computational analysis of the BMPD compound. Using quantum chemical calculations and first-principle simulations, we delved into the structural and electronic properties of BMPD as well as the interfacial adsorption mechanisms between the studied molecule and the iron surface.